Destination Image, Memorable Tourism Experience, and Tourist Satisfaction as Determinants of Revisit Intentions in Rammang-Rammang Tourism Village - Wahyuni; I Nyoman Sudiksa; Hanugerah Kristiono Liestiandre (LP2M IAIN Palopo, 2025)
This study explores how destination image, memorable tourism experience (MTE), and tourist satisfaction influence revisit intentions to Rammang-Rammang Tourism Village, South Sulawesi. A survey of 380 tourists was analyzed using PLS-SEM. Results reveal that destination image and MTE significantly affect revisit intention, while tourist satisfaction serves as both a direct predictor and partial mediator. These findings suggest that strong perceptions and meaningful experiences, when reinforced by satisfaction, enhance tourists’ loyalty. The model shows moderate to strong explanatory power, with predictive relevance confirming its robustness. The study contributes to tourism behavior literature by demonstrating the mediating role of satisfaction between image, experience, and loyalty. For practice, it emphasizes the need for destination managers to align promotional images with authentic experiences, improve infrastructure and services, and design participatory community-based programs. Such strategies not only strengthen revisit intentions but also support sustainable tourism development in Rammang-Rammang.